Battling HIV/AIDS : A Decision Maker's Guide to the Procurement of Medicines and Related Supplies - Tayler, Yolanda (Washington, DC, 2013)
This Guide sets out principles and advice for the procurement of HIV/AIDS medicines and related supplies for programs scaling up antiretroviral therapy (ART) and associated health services, such as basic and palliative care, disease prevention, treatment of opportunistic infections, and laboratory tests. ART includes the treatment of infected adults and children and the prevention of mother-to-child transmission. A wide range of other commodities-particularly condoms and support for basic living and care-are also essential to support the treatment and prevention of HIV. The primary audience for this guide is World Bank staff and those responsible for procuring HIV/AIDS medicines and related supplies in Bank-funded programs and projects-which could include either procurement agency staff or technical agency staff. Policymakers and Bank partners will also benefit from the information and advice in the guide.